ANALISIS ASPEK MAKNA TUJUAN DALAM SLOGAN LALU LINTAS DI KABUPATEN MEMPAWAH: TINJAUAN SEMANTIK - Ainul Pratiwi; Ahmad Rabi’ul Muzammil; Agus Syahrani (Universitas Tanjungpura, 2021)
AbstractThe problem in this research is regarding the form and meaning of the general purpose of traffic slogans in Mempawah Regency, as well as the implementation of the meaning of the traffic slogan objectives in Mempawah Regency as a supplement to the Indonesian language learning text material for the 2013 Curriculum. namely to discuss the category of forms and meanings of traffic slogans in Mempawah Regency. The method used is descriptive. The form of this research is qualitative. Sources of data in this study are slogans along the road in Mempawah Regency from Wajok Hulu Village to Sungai Duri Village 1. Data collection techniques are using observation techniques and documentary study techniques. Based on allthe data obtained regarding traffic slogans, the results of data analysis can be concluded that the 26 traffic slogans in Mempawah Regency were found to contain elements of the aspect of themeaning of the goal which have 5 categories of aspects of the meaning of the goal including (imperative, declarative, pedagogical, narrative, persuasive). This research is related to the 2013 curriculum in Indonesian language subjects in SMP class VIII odd semesters which are suggested for.Keywords: Slogan, Traffic, Mempawah